Waste: The debris of a post-political global society - Jørgen Veisland (Economic and Environmental Studies (E&ES), 2013)
The author gives some philosophical reflections on the issue of ever increasing amount of waste in the context of the believe that technology can solve any problem, while itself being one of the sources of the problem.
Keywords: 330; waste; environmental philosophy